2023
DOI: 10.1002/oby.23667
|View full text |Cite|
|
Sign up to set email alerts
|

Sleep variability and regularity as contributors to obesity and cardiometabolic health in adolescence

Abstract: Objective: Adolescence is a developmental stage of critical changes in sleep and its circadian timing when the contribution of abnormal sleep variability (amount) and sleep regularity (timing) to obesity and its associated adverse cardiometabolic health outcomes appears to increase. The aim of this study was to summarize findings from studies conducted in adolescents examining both sleep variability and regularity in relation to obesity and cardiometabolic health. Gaps in research and potential causal pathways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 105 publications
0
9
0
Order By: Relevance
“…The underlying mechanism may involve sociocultural and biological influences. Adolescents within the sleep irregularity and variability cluster may have irregular breakfast behaviors, which were associated with higher TG [7,37]. Additionally, it may be explained by increased absorption of dietary lipids with increased de novo synthesis of TG in the liver or decreased ability to catabolize absorbed dietary fat in male individuals with sleep deprivation [38].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The underlying mechanism may involve sociocultural and biological influences. Adolescents within the sleep irregularity and variability cluster may have irregular breakfast behaviors, which were associated with higher TG [7,37]. Additionally, it may be explained by increased absorption of dietary lipids with increased de novo synthesis of TG in the liver or decreased ability to catabolize absorbed dietary fat in male individuals with sleep deprivation [38].…”
Section: Discussionmentioning
confidence: 99%
“…Duan et al also observed a relationship between short sleep and high TG (≥1.24 mmol/L) only in adolescent boys [36]. Furthermore, a recent review supported associations of greater sleep variability and irregularity with obesity and adverse cardiometabolic health in adolescence [7]. The underlying mechanism may involve sociocultural and biological influences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among youth, Morales‐Ghinaglia and Fernandez‐Mendoza reported on the influence of inconsistent sleep patterns across nights on metabolic disease risk and proposed standard definitions for different metrics of sleep regularity and variability [28]. The authors concluded that nightly deviations in both the timing and duration of sleep in adolescents related to adverse metabolic outcomes, and they put forth important next steps to elucidate the direct and indirect effects of night‐to‐night variability in sleep duration and irregularity of sleep timing.…”
Section: Sleep Timing and Regularity As Predictors Of Metabolic Healt...mentioning
confidence: 99%
“…Recent reviews also reported that having a later sleep timing midpoint (i.e. wake‐time – ½ sleep duration), as well as greater day‐to‐day sleep duration and sleep timing variability are associated with greater adiposity and adverse cardiometabolic outcomes (Chaput et al, 2020; Morales‐Ghinaglia & Fernandez‐Mendoza, 2023). Consistent evidence suggests that emerging adults and college students with shorter sleep duration and/or poorer sleep quality have greater adiposity (Bailey et al, 2014; Fernström et al, 2020; Kahlhöfer et al, 2016; Krističević et al, 2018; Meyer et al, 2012; Peltzer & Pengpid, 2017; Quick et al, 2014; Sa et al, 2020; Vargas et al, 2014; Yang et al, 2020), but much of this evidence is limited to self‐reported sleep variables and/or using body mass index (BMI) as a single indicator of adiposity/obesity.…”
Section: Introductionmentioning
confidence: 99%